An APEC trade agenda? the political economy of a free trade area of the Asia-Pacific - Morrison, Charles Edward 1944-; Pedrosa, Eduardo (Institute of Southeast Asian Studies, 2007)
Assesses the political feasibility of the Free Trade Area of the Asia-Pacific (FTAAP) proposal and looks at alternative modalities for achieving free trade and investment in the Asia-Pacific. This report includes trade policy perspectives from the three largest economies of the region: the United States, China, and Japan.